Influenza A virus infection induces indoleamine 2, 3-dioxygenase (IDO) expression and modulates subsequent inflammatory mediators in nasal epithelial cells. (1st February 2020) - Lin, Yi-Tsen; Lin, Chih-Feng; Yeh, Te-Huei
Abstract: Background: Nasal epithelial cells are the first site of encounter of the influenza virus, and their innate immune response might define subsequent inflammatory direction. Aims/objectives: We used metabolomics analysis to identify metabolic changes and the regulation of inflammatory cytokines in nasal epithelial cells upon influenza virus infection. Material and methods: We cultured nasal epithelial cells using air-liquid interface (ALI) model. Influenza virus (PR8) infection followed by metabolomic analysis was performed. Furthermore, cytokine expression was analyzed by cytokine array and RT-qPCR. Results: Metabolomic analysis revealed depletion of the tryptophan and accumulation of its metabolite, kynurenine, within 48 h. The major enzyme involved in the tryptophan metabolic pathway, indoleamine 2, 3-dioxygenase (IDO), was overexpressed after infection. Cytokine expression array after infection showed increased levels of IL-1α, CCL2, IL-6, CXCL10, CCL5, and CXCL11, and after using 1-methyltryptophan (1-MT) as inhibitor, the expression levels of IL-6 and G-CSF were reduced. Conclusions and significance: Viral infection results in depletion of tryptophan and accumulation of kynurenine via increased cellular IDO activity. Inhibition of IDO activity or replenishment of tryptophan by local application may be a good therapeutic strategy for limiting the initial damage caused by influenza virus in nasal epithelial cells.